2009
DOI: 10.2527/jas.2008-1348
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sanitary status degradation and dietary tryptophan content on growth rate and tryptophan metabolism in weaning pigs1

Abstract: Health degradation modifies Trp metabolism through induction of Trp catabolism. This could limit the amount of Trp available for growth. The aims of the present experiment were to investigate the effects of a low grade inflammation and dietary Trp on growth and Trp metabolism. Eighty weaned pigs were assigned to 4 experimental treatments according to a 2 x 2 factorial arrangement: 2 sanitary statuses x 2 dietary Trp contents. The Trp content was deficient (low-Trp: 2.4 and 1.9 g of Trp/kg of the phase I and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 28 publications
2
40
0
5
Order By: Relevance
“…The other acute-phase protein, haptoglobin, follows the same time course as CRP after a turpentine injection or a surgical trauma (Alava et al, 1997) but persists for a longer time in plasma after an infection with Actinobacillus pleuropneumoniae (Heegaard et al, 1998). Haptoglobin seems more relevant as a marker for chronic infiammation, general pig health, and sanitary status of the environment (Le Floc'h et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The other acute-phase protein, haptoglobin, follows the same time course as CRP after a turpentine injection or a surgical trauma (Alava et al, 1997) but persists for a longer time in plasma after an infection with Actinobacillus pleuropneumoniae (Heegaard et al, 1998). Haptoglobin seems more relevant as a marker for chronic infiammation, general pig health, and sanitary status of the environment (Le Floc'h et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies include the experiment of Coates et al (1963) with chickens housed in a germ-free environment and more recent studies comparing pigs reared in good or poor sanitary conditions (Le Floc'h et al, 2009;Le Floc'h et al, 2010). Such changes result essentially from the reduction in feed intake, the redistribution of nutrients from growth towards the immune system response (Johnson, 1997;Spurlock, 1997;Le Floc'h et al, 2004), and the decrease in nutrient digestibility (Le Floc'h et al, 2014).…”
Section: Voluntary Feed Intake and Growth Performancementioning
confidence: 99%
“…Poor hygienic conditions reduce growth performance of the pigs (Le Floc'h et al, 2009;Montagne et al, 2012). In the current research, the most noticeable differences observed between both groups of pigs were the greater ADFI and lower PWD in pigs reared under OHC, which resulted in pronounced improvements in ADG without any major effect on feed efficiency.…”
Section: Hygienic Conditions Of the Barnmentioning
confidence: 99%
“…Goodband et al (2014) suggested that an increase in the pathogen load in the environment stimulates proinflammatory cytokine production and endocrine shifts, resulting in a decrease in ADFI. In this respect, Le Floc'h et al (2009) suggested that the reduced growth rate observed in pigs kept under PHC was associated with a greater inflammatory response. In addition, PHC increase bacterial density in the barn and reduce microflora diversity in the GIT, reducing health status and growth performance of the piglets (Montagne et al, 2012).…”
Section: Hygienic Conditions Of the Barnmentioning
confidence: 99%